High temperature stress tolerance in Indian mustard (Brassica juncea) germplasm as evaluated by membrane stability index and excised-leaf water loss techniques (Journal of Oilseed Brassica, 2026)
A total of 796 Indian mustard [Brassica juncea (L.) Czern and Coss.] germplasm accessions including 4 checks were evaluated in augmented block design for their per se performance with respect to their high temperature stress tolerance at seedling stage. The traits assessed were percent population survival at 10 and 25 days after sowing, percent membrane stability index, percent relative water content, percent excisedleaf water loss, percent oil content, 1000- seed weight (g) and seed yield per plant (g). Eighty seeds of each germplasm including four checks were sown in the field under heat stress (26th September) conserved moisture conditions during Rabi 2012-13 in single rows of two metre length. Among all germplasm accessions tested, only 48 germplasm accessions were identified on the basis of percent population survival at 10 DAS (41.00C maximum temperature at 0-10 cm depths), and 25 DAS (40.20C maximum temperature at 0-10 cm depths). Correlation coefficients between seed yield per plant and heat stress traits indicated that seed yield per plant was positively associated with membrane stability index (r=0.282*), and 1000 seed weight (r=0.417**). On the basis of per se performance, germplasm accessions DRMR-1574, DRMR-1624, DRMR-1600, DRMR-1799 and Urvashi found to be tolerant to heat stress could be included in the breeding programme genotypes for high temperature stress conditions.